Level of Satisfaction of Patients With Dental Care Services Provided by Dental Clinic of Shahrekord University - Behrad Tanbakuchi; Masoud Amiri; Sara Valizadeh (Shahrekord University of Medical Sciences, 2018)
Background and aims: Level of satisfaction and opinion of patients are important factors that might be considered in assessing the quality of health care services. This study aimed to assess the level of satisfaction of patients who visited dental clinic of School of Dentistry, Shahrekord University of Medical Sciences, Shahrekord, Iran. Methods: This descriptive, analytical, cross-sectional study was conducted in 2015 on 400 randomlyselected patients visiting Endodontics, Periodontics and Implant, Pediatric Dentistry and Operative Dentistry Departments of Dental Clinic of School of Dentistry, Shahrekord University of Medical Sciences. A questionnaire encompassing demographic information and perspectives on dental care, some clinic-related factors, quality of received services, waiting time, and behavior of dental clinicians and personnel was filled out by the patients. Data were analyzed using SPSS version 22.0. Results: Of all the patients, 77% (n=310) reported improvement in their conditions and were completely satisfied with the received services; 12% reported worsening conditions and so they were dissatisfied with the treatments; and 19.5% (n=78) reported no change in their conditions. The highest level of satisfaction was related to quick presence of dental clinicians and their behavior. Patients were mainly dissatisfied with the treatment costs and welfare services. Conclusion: Satisfaction of patients with the services provided by the dental clinic of School of Dentistry, Shahrekord University of Medical Sciences was at an acceptable level. Items causing dissatisfaction in the patients should be properly addressed in order to maximize the satisfaction rate of patients with the services provided in this clinic.